2010
DOI: 10.1084/jem.20092594
|View full text |Cite
|
Sign up to set email alerts
|

The surface protein HvgA mediates group B streptococcus hypervirulence and meningeal tropism in neonates

Abstract: Lethal meningitis triggered by the hypervirulent group B streptococcus clone ST-17 is mediated by a novel surface protein called HvgA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
281
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(303 citation statements)
references
References 29 publications
(48 reference statements)
13
281
3
2
Order By: Relevance
“…Among the GBS clones, ST-17 is strongly associated with meningitis in infants. It has been shown that a ST-17-specific surface-anchored protein called hypervirulent GBS adhesin (HvgA) is required for intestinal colonization and translocation across the intestinal barrier and the blood-brain barrier (BBB), leading to meningitis (Tazi et al 2010). The mechanism by which the ST-17 clone crosses the intestinal barrier is still unknown.…”
Section: Paracellular Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the GBS clones, ST-17 is strongly associated with meningitis in infants. It has been shown that a ST-17-specific surface-anchored protein called hypervirulent GBS adhesin (HvgA) is required for intestinal colonization and translocation across the intestinal barrier and the blood-brain barrier (BBB), leading to meningitis (Tazi et al 2010). The mechanism by which the ST-17 clone crosses the intestinal barrier is still unknown.…”
Section: Paracellular Pathwaymentioning
confidence: 99%
“…Many studies have focused on the identification of bacterial and host components involved in microbial interactions with the BBB (Kim 2008). Critical bacterial components have been discovered by screening random mutant libraries (Badger et al 2000;Doran et al 2005), analyzing bacterial transcription profiles during infection (Dietrich et al 2003;Teng et al 2005), and using bioinformatic approaches for whole genome comparisons (Uchiyama et al 2009;van Sorge et al 2009;Tazi et al 2010). Bacterial pili, or fimbriae, have emerged as a common class of adhesins used by many meningeal pathogens, such as E. coli K1 (Teng et al 2005), GBS (Maisey et al 2007;van Sorge et al 2009), and N. meningitides (Kirchner and Meyer 2005) to initiate attachment to brain endothelium.…”
Section: Microbial Adhesion To Bmec and Transcytosis Across The Bbbmentioning
confidence: 99%
See 1 more Smart Citation
“…A seven-gene multilocus sequence typing (MLST) allows for the classification of the majority of GBS strains isolated from humans into five major clonal complexes (CCs) with a recent study by Da Cunha et al showing that the major GBS CCs are primarily derived from a limited number of tetracycline-resistant clones, suggesting a key role of tetracycline resistance in GBS strain emergence (10,11). CC-17 GBS strains have been particularly well studied given their role as the major cause of severe, invasive infant disease (10,12). In contrast, serotype V strains cause a larger percentage of invasive disease in nonpregnant adults compared with neonates (13)(14)(15).…”
mentioning
confidence: 99%
“…L'un de ces variants, BibA, avait été précédemment étudié et sa contribution à l'adhésion de streptocoques du groupe B aux cellules épithéliales avait été montrée [9]. L'autre variant, strictement spécifique des souches ST-17 [7,8], a été désigné HvgA (hypervirulent group B streptococcus adhesin) et nous avons exploré son rôle dans l'infection néonatale au streptocoque du groupe B en combinant des approches in vitro et in vivo [10]. Figure 1B).…”
Section: Symptomatologie Et éPidémiologie Des Infections Néonatales àunclassified